2016
DOI: 10.1093/geronb/gbv113
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perception of Aging and Satisfaction With Children’s Support

Abstract: Objectives: Those with self-beliefs in negative aging may desire a stronger support network to buffer against potential threats and may hence see their current network as less than adequate. This study investigated whether negative self-perception of aging is associated with increased dissatisfaction with children's support. Method: Six hundred and forty Chinese older adults with at least one child and a total of 2,108 adult children rated the degree of support received from each child individually and the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
(51 reference statements)
1
14
0
1
Order By: Relevance
“…Outcomes included low social support, poor social engagement, and social isolation. To illustrate, the negative self-perceptions of aging held by Chinese older persons were significantly associated with dissatisfaction in social support provided by children [67].…”
Section: Impact Of Ageism On Health Of Older Persons: Individual Levelmentioning
confidence: 99%
“…Outcomes included low social support, poor social engagement, and social isolation. To illustrate, the negative self-perceptions of aging held by Chinese older persons were significantly associated with dissatisfaction in social support provided by children [67].…”
Section: Impact Of Ageism On Health Of Older Persons: Individual Levelmentioning
confidence: 99%
“…One other survey in China had further reported that those with more negative perceptions of ageing could feel less satisfied with the support provided by their children, while positive perceptions of ageing were not associated with satisfaction with the given support (Cheng, 2017). In China, because of the type of culture and norms dominating in society, more people live together (Pan et al , 2019), and as a result, parents have higher expectations of their children.…”
Section: Discussionmentioning
confidence: 99%
“…The negative stereotypes of aging influence the perception of the identity of older adults in relation to social support, especially family care and attention, resulting in the expectation of greater social support. Political initiatives to combat age-related prejudice and promote positive aging from childhood are important 24 .…”
Section: Discussionmentioning
confidence: 99%